Is non-invasive brain stimulation effective for cognitive enhancement in Alzheimer's disease? An updated meta-analysis - Šimko, Patrik; Kent, Julia Anna; Rektorova, Irena (Clinical neurophysiology, 2022)
OBJECTIVE: Alzheimer's disease dementia (AD) and its preclinical stage, mild cognitive impairment (MCI), are critical issues confronting the aging society. Non-invasive brain stimulation (NIBS) techniques have the potential to be effective tools for enhancing cognitive functioning. The main objective of our meta-analysis was to quantify and update the status of the efficacy of repetitive Transcranial Magnetic Stimulation (rTMS) and Transcranial Direct Current Stimulation (tDCS) when applied in AD and MCI. METHODS: The systematic literature search was conducted in PubMed and Web of Science according to PRISMA statement. RESULTS: Pooled effect sizes (Hedges' g) from 32 studies were analyzed using random effect models. We found both, rTMS and tDCS to have significant immediate cognition-enhancing effect in AD with rTMS inducing also beneficial long-term effects. We found no evidence for synergistic effect of cognitive training with NIBS. CONCLUSIONS: In AD a clinical recommendation can be made for NEURO-ADTM system and for high-frequency rTMS over the left dorsolateral prefrontal cortex (DLPFC) as probably effective protocols (B-level of evidence) and for anodal tDCS over the left DLPFC as a possibly effective. SIGNIFICANCE: According to scientific literature, NIBS may be an effective method for improving cognition in AD and possibly in MCI.
Keywords: kognice; kognitivní dysfunkce; Transcranial Direct Current Stimulation; lidé; Alzheimer Disease; Alzheimerova nemoc; Humans; Cognition; Brain; transkraniální magnetická stimulace; Cognitive Dysfunction; Transcranial Magnetic Stimulation; přímá transkraniální stimulace mozku; mozek